Quantifying urbanization-induced dynamics of urban sprawl using spatial metrics method in Adama City, Ethiopia - Shimelis Sishah Dagne; Hurgesa Hundera Hirpha; Addisu Teshome Tekoye; Zenebe Reta Roba; Mitiku Badasa Moisa (Cogent Social Sciences)
In the realm of urban development, a comprehensive grasp of the intricate dynamics of urban growth and sprawl is imperative for effective planning. This study aims to quantify the urbanization-induced dynamics of urban sprawl using spatial metrics method in Adama City. Time series Landsat TM, ETM+, and OLI/TIRS datasets were utilized to prepare LULC maps of the study area for the years 1992, 2002, 2012, and 2022 using supervised classification technique. Spatial metrics and Shannon’s entropy were used to determine the degree of urban sprawl. The results demonstrate that agricultural land and forest land were negatively impacted by urbanization-induced changes in land use and cover in Adama City. To that aim, Agricultural and vegetation cover have fallen by 24.82 percent and 19.1 percent, respectively, from 1992 to 2022. This is clear evidence that Adama city is expanding at the cost of agricultural land. The spatiotemporal dynamics of urban sprawl have demonstrated incremental tendencies over the past 30 years, with built-up Class Areas (CA) increasing from 1506.15 hectares in 1992 to 4658.5 hectares in 2022. In conclusion, Adama city has experienced unprecedented sprawl at the cost of agricultural land. Urban planners must therefore plan ahead to execute an effective implementation strategy that will keep up with the rate of urban sprawl.